Performance and Contribution of Japanese and Non-Japanese Financial Institutions in Developing Economies: an Empirical Research in Indonesia - Johan, Suwinto (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2020)
Paper purpose is to analysis the value generated by the Japanese and Non Japanese financial institutions in Indonesia banking from 2013-2018. The paper concentrated on the 16 foreign banks contained of seven affiliates of Japanese banks and nine affiliates of Asian Non-Japanese Banks. The shareholders’ origination will be the independent parameter, and the main financial measurements are the capital structure, credit risk, efficiency, profitability, and firm size, will be the dependent parameter. This paper used non-parametric Mann Whitney Test, besides parametric by Regression of Dummy Variable. The empirical outcomes indicate that there are variances in capital structure, credit risk, efficiency, and firm size. There is no significant variance in profitability ratio. Japanese banks are more noticeable in terms of firm size and well in efficiency ratio and loan to deposit ratio. However, Japanese banks have a higher non-performing credit. The outcomes are significant at a = 1% for capital structure and efficiency ratio.